Expresión ¬(¬(¬a∨¬b∨c)∨¬a¬c∨a¬b)
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
¬(c∨¬a∨¬b)=a∧b∧¬c(a∧¬b)∨(¬a∧¬c)∨¬(c∨¬a∨¬b)=(a∧¬b)∨¬c¬((a∧¬b)∨(¬a∧¬c)∨¬(c∨¬a∨¬b))=c∧(b∨¬a)
c∧(b∨¬a)
Tabla de verdad
+---+---+---+--------+
| a | b | c | result |
+===+===+===+========+
| 0 | 0 | 0 | 0 |
+---+---+---+--------+
| 0 | 0 | 1 | 1 |
+---+---+---+--------+
| 0 | 1 | 0 | 0 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 0 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 0 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+
(b∧c)∨(c∧¬a)
c∧(b∨¬a)
(b∧c)∨(c∧¬a)
Ya está reducido a FNC
c∧(b∨¬a)